2009
DOI: 10.1002/ccd.22326
|View full text |Cite
|
Sign up to set email alerts
|

Complications of low‐dose, echo‐guided alcohol septal ablation

Abstract: This study demonstrates the same early incidence of complete heart block requiring permanent pacemaker implantation (4%) and sustained ventricular arrhythmias following low-dose, echo-guided ASA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 14 publications
2
8
0
13
Order By: Relevance
“…In this issue of the Journal, Veselka et al document their experience regarding complications associated with ASA using relatively smaller volumes of infused ethanol [2]. Prior data from a randomized study from the same institution documented that lower volumes of ethanol had similar salutary effects in diminishing both the left ventricular outflow gradient (LVOTG) and symptom density when compared with those patients randomized to receive a higher volume of alcohol [3].…”
supporting
confidence: 72%
“…In this issue of the Journal, Veselka et al document their experience regarding complications associated with ASA using relatively smaller volumes of infused ethanol [2]. Prior data from a randomized study from the same institution documented that lower volumes of ethanol had similar salutary effects in diminishing both the left ventricular outflow gradient (LVOTG) and symptom density when compared with those patients randomized to receive a higher volume of alcohol [3].…”
supporting
confidence: 72%
“…90, 91 The precise identification of the target septal region has permitted injection of less alcohol without compromising the hemodynamic result. 74,75, 92 Although it is evident that complications decrease with increasing experience, the upper range of reported complications is unacceptably high. 67 Proper training and institutional organization should ensure the safety of alcohol septal ablation, and a deep understanding and extensive experience in clinical assessment and treatment of HOCM patients should be a prerequisite for institutions that offer alcohol septal ablation.…”
Section: Complicationsmentioning
confidence: 99%
“…It should be kept in mind, however, that the post-ASA gradient cannot be regarded as a reliable end point even for basal obstruction. 29 Regardless of the gradient, satisfactory ablation is achieved when sufficient ethanol deposits in septal myocardium attributable to intraventricular obstruction are confirmed by simultaneous TTE. 5 At any rate, latent gradients should be evaluated by the combination of multiple provocation tests which provide different types of modification to the hypertrophied LV because it has often been shown that some patients have susceptibility to one specific provocation.…”
Section: Discussionmentioning
confidence: 99%